Analysis of Government Employee Performance in Keerom Regency, Papua, Indonesia - Henderjeta Meho; Ferdinandus Christian (Journal of Economics, Business, and Government Challenges, 2019)
This study aims to find out and obtain a clear picture of how much influence leadership, motivation, and work discipline have on employee performance in public sector organization. the study was conducted in Keerom Regency, Papua province, Indonesia. The type of data used is qualitative data and quantitative data. Data collection techniques used were field studies and literature studies. The research was conducted using descriptive quantitative data analysis techniques consisting of research instrument tests, standard assumption tests, and multiple regression analysis. The results showed that the only leadership influence the employee performance. Two other variables, motivation and discipline of work do not prove significantly influence on government employee performance in Keerom Regency Office of Industry, Trade and Cooperatives.